2018
DOI: 10.1016/j.ceramint.2017.11.195
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide surface functionalization and related effects on corrosion resistance of titanium implants

Abstract: Important clinical concerns in orthopedics and dental implantology are associated with a significant release of titanium (Ti) metal ions and debris due to the low corrosion resistance of this material. Chemical modifications on Ti surfaces have been performed in order to minimize effects of corrosion. In this contribution, zinc oxide (ZnO) thin films were deposited onto Ti surfaces and functionalized with four different organic bifunctional molecules in order to increase the corrosion resistance. SEM and XPS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 58 publications
(67 reference statements)
7
40
0
Order By: Relevance
“…27 In addition, the surface functionalization of ZnO nanoakes with thiourea can enhance their sensitivity and selectivity, and the ZnO nanoakes exhibit gas sensing characteristics, which pave the way for the realization of highly sensitive and selective ber optic sensors. 28 Trino et al 29 found that the functionalization of ZnO with four different organic bifunctional molecules not only could increase the corrosion resistance in ZnO, but could also lead to different wettabilities and surface energy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…27 In addition, the surface functionalization of ZnO nanoakes with thiourea can enhance their sensitivity and selectivity, and the ZnO nanoakes exhibit gas sensing characteristics, which pave the way for the realization of highly sensitive and selective ber optic sensors. 28 Trino et al 29 found that the functionalization of ZnO with four different organic bifunctional molecules not only could increase the corrosion resistance in ZnO, but could also lead to different wettabilities and surface energy behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial pure titanium grade 4 (Ti cp4 (ACNIS, Brazil)) discs, with a diameter of 12.7 mm and 3 mm of thickness, were prepared and coated with ZnO based in our previous work [10]. Briefly, the ZnO resin was synthesized by sol-gel method dissolving 72.05 g of citric acid in 200 mL of deionized water.…”
Section: Dentin Matrix Protein 1(dmp1) Peptides Depositionmentioning
confidence: 99%
“…After the Ti discs were sandblasted and etched with Piranha solution (a mixture of 7:3 (v/v) 98% H 2 SO 4 and 30% H 2 O 2 ) the diluted ZnO solution was deposited by spin coating technique (2000 rpm during 60 s) [10]. Then, the ZnO surface was functionalized with two different bifunctional molecules 3-mercaptopropionic acid (MPA) and 3-4 aminophenyl propionic acid (APPA) by immersion method [10]. The 2 mM APPA solution was prepared in ethanol absolute by stirring until complete dissolution.…”
Section: Dentin Matrix Protein 1(dmp1) Peptides Depositionmentioning
confidence: 99%
See 2 more Smart Citations